Differential Impact of Coronary Revascularization on Long-Term Clinical Outcome According to Coronary Flow Characteristics: Analysis of the International ILIAS Registry. (23rd May 2022) - Hamaya, Rikuta; van de Hoef, Tim P.; Lee, Joo Myung; Hoshino, Masahiro; Kanaji, Yoshihisa; Murai, Tadashi; Boerhout, Coen K.M.; de Waard, Guus A.; Jung, Ji-Hyun; Lee, Seung Hun; Mejia Renteria, Hernan; Echavarria-Pinto, Mauro; et al.
Abstract : Background: Coronary pressure indices such as fractional flow reserve are the standard for guiding elective revascularization. However, considering additional coronary flow parameters could further individualize and optimize the decision on revascularization. We aimed to investigate the potentially differential prognostic associations of elective percutaneous coronary intervention (PCI) according to coronary flow properties represented by coronary flow reserve (CFR), coronary flow capacity (CFC), and baseline CFC (bCFC). Methods: From the ILIAS Registry (Inclusive Invasive Physiological Assessment in Angina Syndromes) composed of 16 hospitals globally from 7 countries, patients with obstructive coronary artery disease who underwent invasive coronary physiological assessment were included (N=2370 vessels). We assessed effect measure modifications of the association of PCI and 5-year target vessel failure according to CFR, CFC, and bCFC either assessed by Doppler-technique or thermodilution-method. Results: The mean age of the population was 63.3 years, and there were 1322 (73.6%) males. Median fractional flow reserve was 0.85, and PCI was performed in 600 (25.3%) vessels. Reduced CFR, CFC, and abnormal bCFC were defined in 988 (41.7%), 542 (22.9%), and 600 (25.3%) vessels, respectively. Significant effect measure modifications were observed by CFC either in odds ratio ( P =0.0018), additive ( P =0.029), and hazard ratio scale ( P =0.0002). The absolute risk of 5-year target-vessel failure was higher if treated by PCI in vessels with normal CFC by 1.8 (−1.7 to 5.3) percent, while that was lower by −5.9 (−12 to −0.1) percent in those with reduced CFC. CFR and bCFC were not significant effect modifiers in any scales. Similar associations were observed in per-patient analyses, whereas the findings were less robust. Conclusions: We observed qualitative effect measure modification of PCI and 5-year clinical outcomes according to CFC status in additive scale. CFR and bCFC were not robust effect modifiers. Therefore, CFC could be potentially used to optimize the patient selection for elective PCI treatment combined with fractional flow reserve.